New perspectives of biological therapy for severe asthma in adults and adolescents (Swiss Medical Weekly, 2022)
Severe asthma is associated with increased morbidity, mortality, healthcare costs and impaired quality of life. Asthma is no longer considered as a single entity but as a heterogeneous disease with different clinical presentations (phenotypes) and variable underlying mechanistic biological pathways (endotypes). Two different endotypes are based on the inflammatory Type 2 T-helper response: T2-high and T2-low. The understanding of these endotypes has revolutionised the management of severe asthma. Recent guidelines from the 2019 European Respiratory Society/American Thoracic Society (ERS/ATS) and Global Initiative for Asthma (GINA) 2021 specifically address the diagnosis and the management of severe asthma in adults, but less evidence exists for the paediatric population. Presently, five biologics for the treatment of severe asthma are approved, i.e., omalizumab (anti-IgE antibody), mepolizumab and reslizumab (anti-IL-5 antibody), benralizumab (anti-IL-5 receptor antibody) and dupilumab (anti-IL-4 receptor alpha antibody). This article reviews the pathological mechanisms of severe asthma, clinical biomarkers related to the T2-high endotype, and their use for the prediction of the severity of the disease and response to biological therapy. Furthermore, future developments of biologics for severe asthma are presented.